HUBUNGAN STRUKTUR KEPEMILIKAN DAN EXTERNAL MONITORING TERHADAP AGENCY COST DAN ALIRAN KAS - Yustina Ade (University of Merdeka Malang, 2008)
Capital credit was credit given by private/government public bank to solve theproblem of liquidation on companies. In a small company, inhibiting liquidation andinformation which was asymmetric influenced manpower recruitment, especially in managerlevel and it could make adverse selction problem. In agency theory, it was mentioned thatagency problem could appear if there was a different self-interest between (1) capital ownerand manager (2) capital owner and bank. This research was aimed to analyze if ownershipstructure and external monitoring had influence to agency cost and whether agency cost hadinfluence to cash flow. The samples of this research were small companies running inmanufatures, corporation, and which got capital credit. Samples taken were 101 companiesand the analyzes method used was SEM. This research concluded that agency cost was in smallcompanies that the manager was not the capital owner, but there was no indication of moralhazard.